2017
DOI: 10.1093/jrr/rrx025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time interval and dose rate on cell survival following low-dose fractionated exposures

Abstract: Enhanced cell lethality, also known as hyper-radiosensitivity, has been reported at low doses of radiation (≤0.5 Gy) in various cell lines, and is expected to be an effective cancer therapy. We conducted this study to examine the impact of time interval and dose rate of low-dose fractionated exposures with a short time interval. We evaluated the cell-survival rates of V79 and A549 cells using clonogenic assays. We performed fractionated exposures in unit doses of 0.25, 0.5, 1.0 and 2.0 Gy. We exposed the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
8
26
0
2
Order By: Relevance
“…In addition, unlike SD X‐ray, FD irradiating exposure along with time intervals provided more inhibitory effects on metastatic cells. These results were in agreement with Terashima et al (2017) report that FD and short time intervals resulted in stronger cytotoxic effects, possibly due to raise of hyperradiosensitivity of radioresistance tumor cells, than SD exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, unlike SD X‐ray, FD irradiating exposure along with time intervals provided more inhibitory effects on metastatic cells. These results were in agreement with Terashima et al (2017) report that FD and short time intervals resulted in stronger cytotoxic effects, possibly due to raise of hyperradiosensitivity of radioresistance tumor cells, than SD exposure.…”
Section: Discussionsupporting
confidence: 93%
“…XI procedure was carried out by 6‐MV linear accelerator machine (SIEMENS Healthcare Company) at Radiotherapy Center, Vali‐e‐Asr Hospital, Zanjan, according to a plan which was reported by Terashima, Hosokawa, Tsuruga, Mariya, & Nakamura (2017). Briefly, two 96‐well plates were assigned, as shown in Figure 1a: Single dose (SD) and fractionated dose (FD).…”
Section: Methodsmentioning
confidence: 99%
“…This previously observed dose-rate range is different from that we observed in this study. Other potential mechanisms, such as cumulative low-dose HRS after fractionated exposures has a possibility to induce this reversal in radio-sensitivity 57 60 , however the CHO-K1 cell line does not exhibit this behaviour 21 . From the present study and the previous reports, it is likely that the dose-rate range for IDREs related to cell-cycle effects is higher than that related with low-dose HRS.…”
Section: Discussionmentioning
confidence: 99%
“…Tailoring the PLDR parameters, such as the low dose and time intervals between the low doses, can further increase radiosensitivity. 34 Low dose pulses should be applied within the LDHRS range of specific cell type, however, this might not be straightforward. The transition dose from LDHRS to IRR is cell type-specific and has been observed in the range of 0.2 Gy to 0.6 Gy for different tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although enhanced cytotoxic effects were observed with shorter intervals of several minutes between low dose fractions, it is possible to introduce variations in time intervals between consecutive doses, dose per fraction and dose rate. 34 Reduced cell survival can be observed also when low doses are separated by intervals of several hours, and additional benefit can be observed when combining this approach with chemotherapy. [52][53][54][55] In this study, we demonstrated LDHRS in isogenic radioresistant cells, but not in the parental cells.…”
Section: Discussionmentioning
confidence: 99%